UJI SITOTOKSISITAS, ANTIPROLIFERATIF, DAN PENGARUHNYA TERHADAP EKSPRESI P53 DAN BCl2 DARI FRAKSI ETANOL INFUSA DAUN TEH (Camellia sinensis (L.) O.K.) TERHADAP SEL HeLa - Laela Hayu Nurani (Majalah Obat Tradisional, 2011)
Tea (Camellia sinensis  (L.) O.K.)  is one of medical plant traditionally used by society as anticancer. The aim of this research is to evaluate the citotoxic and antiproliferative effect of ethanolic fraction of tea (Camellia sinensis  (L.) O.K.) and its effect on P53 and bcl-2. Tea were collected and extracted by infundation and fractioned with ethanol as solvent. Citotoxicity test was done by incubating HeLa cell at a density of 2.104 with treatment using extract in concentration of 250; 125 ; 62,5; 31,25; 15,63; and 7,81 µg/mL during 24 hours.  Antiproliferative test were done by calculating doubling time which was equaling a life cell on treatment sample concentration 31,25 µg/mL; 15,63 µg/mL; 7,81 µg/mL; and 3,91 µg/mL with cell control at 24, 48 and 72 hours.  Imunohistochemistry assay was used in LC50  with p53 and bcl-2 antibody. P53 and bcl-2 expression is compared to control. The result indicated that ethanol fraction of tea (Camellia sinensis  (L.) O.K.) leaf infuse has citotoxicity effect on HeLa cell with LC50 of 24,45 µg/mL. The result of  doubling time test indicated that doubling time value for a solvent  control is 74,11 hours and a cell control is 78,22 hours. While, with treatment 31,25 µg/mL; 15,63 µg/mL; 7,81 µg/mL; and 3,91 µg/mL resulted on negative slope then did not produce doubling time. The extract can induce p53 expression and inhibit bcl-2  expression compared to control.